2022
DOI: 10.1007/s12281-022-00446-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Invasive Fungal Infections in Solid Organ Transplant Recipients: an Indian Perspective

Abstract: Purpose of Review This review summarizes the available Indian data on epidemiology of invasive fungal infections (IFI) in recipients of solid organ transplants (SOT). The epidemiology is further compared with studies from other parts of the world for each SOT type. Recent Findings The available studies on Indian epidemiology of IFI in SOT are scarce, though the number of SOTs performed in India have increased tremendously in recent years. The limited data from India pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Indeed, while Candida albicans and Aspergillus spp. remain the most important pathogens in SOT and HSCT, a rising emergence of non- C. albicans and non- Aspergillus infection has recently been noted [ 12 ]. The Transplant-associated infection Surveillance Network (TRANSNET), a global repository of data on transplant patients followed-up prospectively over a six-year period (from 2001 to 2006), found that the risk of IFIs in SOT varied with the organ type, being highest in small bowel (11.6%), followed by lung (8.6%), liver (4.7%), heart (4%), pancreas (3.4%), and kidney (1.3%) [ 5 ].…”
Section: Overview Of the Epidemiology Of Ifis In Sot And Hsctmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while Candida albicans and Aspergillus spp. remain the most important pathogens in SOT and HSCT, a rising emergence of non- C. albicans and non- Aspergillus infection has recently been noted [ 12 ]. The Transplant-associated infection Surveillance Network (TRANSNET), a global repository of data on transplant patients followed-up prospectively over a six-year period (from 2001 to 2006), found that the risk of IFIs in SOT varied with the organ type, being highest in small bowel (11.6%), followed by lung (8.6%), liver (4.7%), heart (4%), pancreas (3.4%), and kidney (1.3%) [ 5 ].…”
Section: Overview Of the Epidemiology Of Ifis In Sot And Hsctmentioning
confidence: 99%
“…The primary mode of acquiring mold infections is inhalation of fungal airborne spores. The resulting IFIs are predominantly observed in lung transplant recipients and are associated with higher mortality due to the frequent multiresistance of these fungi [ 12 ].…”
Section: Overview Of the Epidemiology Of Ifis In Sot And Hsctmentioning
confidence: 99%
“…During the last few decades, the rate of fungal infections have been rising tremendously (Sharma et al, 2022). The estimated global rate of invasive fungal infections is 1.5 million yearly, this rising frequency may be attributed to the wide use of broad-spectrum antibiotics as well as the increased number of immunocompromised individuals due to organ transplantation, HIV infections or cancer patients on chemotherapy (Bajpai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%